Kemampuan Pemecahan Masalah dan Gaya Kognitif Siswa pada Model Pembelajaran Project Based Learning - Suciawati, Vici; Sudianto, Sudianto; Jatisunda, Moh Gilar; Rohaeti, Titi (Polinomial : Jurnal Pendidikan Matematika, 2022)
This study aims to determine differences in problem-solving abilities and cognitive styles of students in the project based learning model with conventional learning. This research is a quantitative research with an experimental approach. The population in this study is class XI of State Vocational High School 1 Majalengka 2021/2022. The sampling technique was carried out randomly, namely class XI-1 as the experimental class and class XI-2 as the control class with a total of 33 people and 36 people in each class. The instruments used in this study were questionnaires and tests. The results showed that there were differences in problem-solving abilities and students' cognitive styles between the experimental class using the project based learning model and the control class using conventional learning. Classes that get a project based learning model are better than conventional learning. This is because in the project based learning model students are given the freedom to plan learning activities, carry out projects collaboratively, and ultimately produce work products that can be presented to others.